ASPEK PENGAWASAN CORPORATE GOVERNANCE TERHADAP TINGKAT PENGUNGKAPAN LINGKUNGAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE TAHUN 2014-2018) - Rihan Mustafa Zahri (Management Insight: Jurnal Ilmiah Manajemen, 2020)
This research aims to obtain empirical evidence about the role of corporate governance oversight on environmental disclosure. The independent variables tested in this research consisted of the corporate governance oversight aspects (proportion of BOC independent, ethnic background of president BOC, ducational background of president of BOC, frequency of meeting BOC, proportion of committee audit independent, frequency of meetings audit committee, diversity gender of BOC), while the dependent variable is environmental disclosure measured by using GRI 4.0. The sample of this research consist of 89 manufacture companies listed in stock exchange of Indonesia from 2014-2018. This research is quantitative research which the sampling method is purposive sampling. Data of corporate governance aspects were collected from annual reports and analysis of this research is multiple regression analysis. The result of this research showed that ethnic background of BOC have negative significant, proportion of committee audit independent have positive significant, frequency of meetings audit committee have positive significant on environmental disclosure.Keyword: corporate governance oversight aspects; Environmental disclosure